Growth, Yield, Oil Content and Composition of Cymbopogon Jwarencusa in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2007)
Cymbopogon jwarencusa, an aromatic grass recently introduced in Bangladesh was studied for its growth, yield, oil content and composition of the oil. The herbage yield and oil content were highest in 2nd and 1st cutting respectively. Among the thirty three compounds identified by GC- MS, piperitone (85 %) was the single major compound in the oil. Among others, eucalyptol (2.2 %), camphene (2 %) and β-elemene (1.4 %) are mentionable. Bangladesh J. Sci. Ind. Res. 41(1-2), 97-100, 2006